(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
The organochlorine pesticides (OCPs) have high toxicity in human and animals. They present bioacumulation and biomagnification effects in adipose tissue, through de food chains. The analysis of OCP’s in fatty samples can be used as an evaluation risk parameter of environmental pollution; however this analysis is not commonly included in routine monitoring programs due the complexity of the matrix. Different extraction solvent and clean up sorbent material such as C18, florisil and silica were evaluated for the extraction of OCP’-s from adipose tissue samples. The extracts obtained were analyzed by gas chromatography with micro-electron capture detector (GC-μECD). Ultrasonic Assisted Extraction (UAE) was validated for a multiresidues method of 20 organochlorine pesticides. The limits of detection (LOD) were below of 0,58 ppb and limits of quantification ranging from 1,75-0,45 ppb. The average recoveries of the validated method were 86,2% .